Pengaruh Model Pembelajaran Project Based Learning Terhadap Keterampilan Kolaborasi Dan Kreativitas Siswa Pada Materi Struktur Dan Fungsi Jaringan Tumbuhan Di Kelas Xi Sma Negeri 1 Kabila: (The Influence of the Project Basic Learning Model on Students' Collaboration and Creativity Skills on the Material of Plant Tissue Structure and Function in Class XI of SMA Negeri 1 Kabila) - Menanti, Menanti; Ahmad, Jusna; Usman, Nurul Fajryani; Dama, Lilan; Febriyanti, Febriyanti; Pagalla, Devi Bunga (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2025)
The purpose of this research is to determine the effect of the Project-Based Learning model on Collaboration and Creativity Skills in XI grade students of SMA Negeri 1 Kabila. This research is an experimental quantitative study with a (Nonequivalent Control Group Design). The sample in this study consisted of 20 students. The data analysis technique was complemented by statistical data processing methods. The average pretest score for Collaboration Skills in the experimental class was 37.60, while in the control class it was 35.20. The average pretest score for Creativity Skills in the experimental class was 30.20, and in the control class, it was 28.20. Meanwhile, the average posttest score for Collaboration Skills in the experimental class was 44.25, and in the control class, it was 37.20. The average posttest score for Creativity Skills in the experimental class was 37.05, and in the control class, it was 29.00. These results indicate that there is a significant effect before and after the treatment. Based on the t-test results with a t-table value of 2.086, the influence value for collaboration skills is 2.548 and the influence value for creativity skills is 14.209. In other words, t calculated > t table, thus H0 is rejected and H1 is accepted. There is an effect of the Project Based Learning Model on Collaboration and Creativity Skills of Students in the Material of Structure and Function of Plant Tissues in Class XI of SMA Negeri 1 Kabila. Abstrak. Tujuan penelitian ini adalah untuk mengetahui pengaruh model Project Based Learning terhadap Keterampilan Kolaborasi dan Kreativitas pada Siswa Kelas XI SMA Negeri 1 Kabila. Penelitian ini merupakan penelitian eksperimen kuantitatif dengan jenis penelitian (Nonequivalent Control Group Design). Sampel dalam penelitian ini sebanyak 20 siswa. Teknik analisis data dilengkapi dengan metode pengolahan data statistik. Rata-rata pretest Keterampilan Kolaborasi kelas eksperimen sebesar 37,60 dan kelas kontrol sebesar 35,20. Rata-rata pretest Keterampilan Kreativitas kelas eksperimen sebesar 30,20 dan kelas kontrol sebesar 28,20. Sedangkan rata-rata posttest Keterampilan Kolaborasi kelas eksperimen sebesar 44,25 dan kelas kontrol sebesar 37,20. Sedangkan rata-rata posttest Keterampilan Kreativitas kelas eksperimen sebesar 37,05 dan kelas kontrol sebesar 29,00. Hasil tersebut menyatakan bahwa terdapat pengaruh yang signifikan sebelum dan sesudah perlakuan. Berdasarkan hasil uji-t dengan t tabel yaitu sebesar 2,086, diperoleh nilai pengaruh untuk keterampilan kolaborasi sebesar 2,548 dan nilai pengaruh untuk keterampilan kreativitas sebesar 14,209. Dengan kata lain t hitung > t tabel, maka H0 ditolak dan H1 diterima. Terdapat Pengaruh Model Project Based Learning terhadap Keterampilan Kolaborasi dan Kreativitas Siswa pada Materi Struktur dan Fungsi Jaringan Tumbuhan Kelas XI SMA Negeri 1 Kabila.